Systematic Literatur Review (SLR) : Pemanfaatan Software Photomath Dalam Pembelajaran Matematika - Tasya Aulia Faisal; Yahfizham Yahfizham (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to analyze meta data related to the use of Photomath application as a computational implementation in the form of mathematical software, namely by looking at the research objectives that relate mathematical solutions using the application. This research used the Systematic Literature Review (SLR) method. This systematic review identified 7 studies through the Google Scholar database published in 2020-2024. Data collection was carried out by collecting all articles related to the use of photomath in solving mathematical problems with selection criteria and using the PRISMA protocol as a research instrument guideline. The results showed that math software, namely photomath, can make it easier for students, especially those who are not proficient in learning math, this software can help solve math problems practically by taking pictures, this application can also be used as a virtual learning media, teaching materials related to many materials such as decimals, fractions, arithmetic, simple linear equations, algebra to simple calculus.